Improving Students' Vocabulary Using Flashcards at SMP N 2 Tondano - Rogi, Deva Eklesia; Tuerah, Ignatius J. C.; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
One of the language components that students studying a foreign language need to grasp is vocabulary. A vocabulary is a list of words with meanings that we use to communicate our emotions and ideas through language. This implies that kids can produce a greater number of sentences both in writing and speaking if they have a strong vocabulary. Among the many instructional resources available for vocabulary instruction is the use of flashcards. The purpose of this study was to determine how well flashcards work for increasing pupils' vocabulary. Twenty seventh-grade students from SMP Negeri 2 Tondano participated in this study. Pre-experimental design with one group undergoing pre- and post-testing was employed in this study. The study's findings indicate that using flashcards can help pupils' vocabulary grow. The average pre-test score was 5.65, while the average post-test score was 7.55. These results indicated a significant difference between the pre- and post-test scores, indicating that flashcards significantly improve student achievement in terms of vocabulary mastery for grade VII students at SMP Negeri 2 Tondano. It is advised that educators teach vocabulary to their students using flashcards.